Relationship between T lymphocyte subsets and cortisol in systemic lupus erythematosus - Shah, D; Kiran, R; Wanchu, A; Bhatnagar, A (Kathmandu University Medical Journal, 2010)
Background: Systemic Lupus Erythematosus (SLE) is a complex chronic immunological disease characterized by increased B cell activity and altered T cell function. Objective: To investigate relationship between T lymphocyte subsets and cortisol with the disease activity of systemic lupus erythematosus patients in North India. Materials and methods: The percentage of CD4+ and CD8+ T cells in the lymphocyte of SLE patients and healthy controls were determined by flow cytometry. Serum cortisol of SLE patients and healthy controls was determined by enzyme-linked immunosorbent assay (ELISA). Results: A significant decrease in the percentage of CD4+ T cells and increase in the percentage of CD8+ T cells were found in patients with SLE compared to the healthy controls. Decrease in the ratio of CD4+/CD8+ T cell and low level of serum cortisol were found in the patients with SLE. The ratio of CD4+/CD8+ T cell was inversely correlated with systemic lupus erythematosus disease activity index (SLEDAI) score and erythrocyte sedimentation rate (ESR). A positive correlation was observed between CD8+ T cells and SLEDAI score. Furthermore, CD8+ T cells were positively correlated with ESR in the patients with SLE. Conclusion: The results showed that low level of cortisol and high percentage of CD8+ T cells in the lymphocytes could be actively involved in the pathogenesis of SLE. Key words: CD4+/CD8+ T cell ratio; cortisol; systemic lupus erythematosus; T-cell activation DOI: 10.3126/kumj.v7i3.2726 Kathmandu University Medical Journal (2009) Vol.7, No.3 Issue 27, 213-219